THE INFLUENCE OF EXCHANGE RATES AND INFLATION ON EXPORTS IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Exports play a crucial role in a country's economic growth. Exports are influenced by various macroeconomic factors, primarily exchange rates and inflation. Exchange rate depreciation can increase export competitiveness, and conversely, exchange rate appreciation can reduce competitiveness. Inflation affects export performance, where high inflation increases production costs and reduces the competitiveness of export goods. This research is crucial for understanding the impact of exchange rates and inflation on Indonesian exports. Data in the form of a time series period 1993-2023 obtained from World Development Indicators (WDI). The variables used include exchange rates, inflation, and exports of Goods and Services. Using a quantitative approach with econometric analysis, specifically multiple linear regression, to determine the cause-and-effect relationship between variables. The results of the study indicate that simultaneously, exchange rates and inflation have a significant effect on exports. Partially, the results of the study show that inflation has a negative and significant impact on Indonesia's exports. In contrast, the exchange rate does not exhibit a significant influence on exports.
Keywords: Exchange Rate; Inflation; Indonesian Exports; Time Series